SIFAT ORGANOLEPTIK DAGING AYAM PETELUR TUA YANG DIRENDAM DALAM EKSTRAK KULIT NANAS (Ananas comosus L. Merr) - Dewanto, Ahmad; Rotinsulu, M. D.; Ransaleleh, T. A.; Tinangon, R. M. (Universitas Sam Ratulangi, 2017)
The objective of this study was to evaluate the organoleptic characteristic of old laying meat immersed in pineapple peel extract (Ananas comusus L. Merr). The materials used in this study were 25 birds of the age of 24 months old and the extract of 10 pineapple peels. The Completely Randomized Design was applied in this study, involving the organoleptic test measurement with hedonic scale and untrained panelist of 40 peoples. Treatments were involving immersion of old laying meat in pineapple peel extract with levels:R0 = Without immersion in pineapple peel extract; R1 = Immersion in pineapple peel extract during 1 hour; R2 = Immersion in pineapple peel extract during 2 hours; R3 = Immersion in pineapple peel extract during 3 hours; R4 = Immersion in pineapple peel extract during 4 hours. Analysis of variance were used for organoleptic test and showed that treatments affected significantly (P<0.01) the colour, flavour, tenderness, texture, and taste of ald laying meat. Study indicated that panelists preferred the texture and tenderness of laying meat immersed during one hour in pineapple extract however they preferred the meat colour and taste without immersion.Keywords: Laying meat, pineapple peel, organoleptic